A synthesis of priorities, patterns, and gaps in large carnivore corridor research - Bhatt, Tek Raj; Castley, J. Guy; Baral, Hem Sagar; Chauvenet, Alienor (Frontiers in Conservation Science, 2023)
Conservation research plays an integral role in the effort to conserve biodiversity globally. However, research gaps can limit conservation research's potential contribution to addressing global biodiversity problems such as habitat fragmentation. While a synthesis of the research literature does not attain effective conservation action by itself, it can inform future research and corridor conservation planning and practices. We used a systematic search of peer-reviewed research articles in Scopus, Web of Science, and grey literature in the Connectivity Conservation Specialist Group library published before December 2020. Our review assessed research on the identification and use of corridors, a primary instrument used to address the threats of habitat fragmentation, for large carnivores to identify patterns, priorities, and gaps in the literature. We focused on large carnivores because they are frequently used for connectivity planning owing to their higher sensitivity to habitat fragmentation and their importance as conservation flagship species. We found that peer-reviewed studies primarily focused on single-species corridors with a strong preference toward apex predators, whereas grey literature focused on multi-species corridors. More than 80% of studies included one of the following five species, the mountain lion (n=46 studies), American black bear (n=31 studies), jaguar (n=25 studies), tiger (n=25 studies), and brown bear (n=18 studies). Although research on the identification of corridors was relatively more common in the past, we found an increasing trend in the publication of studies assessing the use of corridors by large carnivores in recent years. The published research is predominantly from the North America (47%) and Asia (30%), with comparatively fewer studies from Africa (4%), despite having several large carnivore species. While climate change and human-wildlife conflict are considered major concerns for large carnivore conservation, these were seldomly considered in corridor research. Corridor research collaborations exist between academia, government, and non-government institutions, but the involvement of the private sector is lacking. Our review shows that there is scope for future corridor research to (i) focus on areas where geographical gaps exist, (ii) target multi-species corridors, (iii) include climate change and human-wildlife conflict scenarios, and iv) increase collaboration with the private sector to better inform connectivity solutions.